Growth-hormone-releasing Hormone as a Prognostic Biomarker and Therapeutic Target in Gastrointestinal Cancer - Mehrabadi, Shima; Velayati, Mahla; Zafari, Nima; Hassanian, Seyed M.; Mobarhan, Majid Ghayour; Ferns, Gordon; Khazaei, Majid; Avan, Amir (Current Cancer Drug Targets, 2023)
Gastrointestinal cancers are prevalent cancers in the world with a poor prognosis, causing about one-half of all cancer deaths in the world. Unfortunately, there is no effective treatment for GI cancers. GHRH and GHRH receptors (GHRH-R) are expressed in various tumoral tissues and cell lines. The inhibition of GHRH-R is a new area of research because it provides a possible means of treating several types of cancer. Recent publications have reported GHRH and GHRH-R expressions in breast, pancreatic, prostate, colon, gastric, ovarian, and lung cancers, along with promising data about the use of GHRH antagonists in the treatment of different cancers. This review aims to summarize the recent studies on the relationship between GHRH and GI cancers and assess whether this hormone can be our target for therapy or used as a prognostic marker for GI cancers.
Keywords: prognostic